Three-dimensional dynamic modeling and analysis of moving elevator traveling cables. (March 2017) - Zhu, WD; Fan, W; Mao, YG; Ren, GX
This paper addresses three-dimensional dynamic modeling of an elevator traveling cable with bending and torsional stiffnesses and arbitrarily moving ends. Two different types of elements are introduced to model the traveling cable: one is based on Rayleigh beam theory and the other Kirchhoff plate theory. Dynamic equations of motion, which are presented as differential algebraic equations, are solved by the backward differentiation formula. Equilibria of a traveling cable with different cable parameters and car positions are first calculated. Motions of cable ends are prescribed next to simulate the free response of the traveling cable due to motion of the car. Finally, effects of different types of building sways on dynamic responses of the traveling cable are examined.